Produção textual em língua inglesa : contribuições das ferramentas multimídia - Lima, Joceval Fonseca (2015)
This dissertation is inserted in the Applied Linguistics line and brings theme the textual production in English language through multimedia tools. The present research investigates the contributions from activities about William Shakespeare and the digital tools to teach and learn the idiom focused. We begin it from the hypothesis that through these resources we might achieve an effective English textual production, promoting an interaction among the students and that way, developing linguistics abilities which are essential for foreign language learning. For that reason, we are going to search for the basis theories which support the English literacy, Language acquisition and Multimidia Resources, considering the works of Lemke (2010), Rojo (2012), Ferraz (2011), Figueiredo (2009), Harmer (1998), Finardi e Porcino (2014), Paiva (2010) Xavier (2008), Dudeney & Hockly, (2007), Araújo (2009), Levy (2010). As follow, we describe how the research in action was done: starting from the project in which was used a Shakespeare Webquest, the students produced a multimidia narrative and also some notes where they could talk about their learning experience with Shakespeare. These notes were shared with one colleague so that each of them could add some extra information in the received text, in a collaborative way, relevant information was added in these notes. These produced texts by the students – the multimidia narratives – the notes and also the collaborative part – were qualitatively analyzed in order to check in what ways the digital resources contributes to develop the English competences. Therefore, this research achieved, emphasizing the importance of this work with English textual production, promote a meaningful construction, contributing to the learning as a whole.